1938
DOI: 10.1084/jem.67.5.809
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Experimental Hypertension

Abstract: The production of the acute malignant phase of experimental hypertension has been accomplished in seventeen dogs. The method used to produce this type of hypertension was the same as for the benign type (4), namely, constriction of the main renal arteries, or the equivalent, constriction of the aorta above the origin of both main renal arteries, but the constriction was especially severe. The malignant phase in the animals was characterized by hypertension, terminal renal insuffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

1938
1938
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(42 citation statements)
references
References 11 publications
5
37
0
Order By: Relevance
“…The thickened arterial walls are thought to lose their ability to constrict, resulting in a resetting of cerebrovascular autoregulation at higher blood pressure levels. 3134 Continued high pressure produces increased capillary hydrostatic pressure with capillary damage, 36 an effect that does not occur in renal arteries protected from hypertension distal to an experimental arterial clamp 36 or to renal arterial stenosis. 30 The overdistension 3738 of these small arteries occurs in segmental fashion with vascular necrosis, [38][39][40] which allow red blood cells, plasma, and protein ultrafiltrates into the stretched segments of the wall.…”
Section: Arterial Pathology Of Lacunesmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickened arterial walls are thought to lose their ability to constrict, resulting in a resetting of cerebrovascular autoregulation at higher blood pressure levels. 3134 Continued high pressure produces increased capillary hydrostatic pressure with capillary damage, 36 an effect that does not occur in renal arteries protected from hypertension distal to an experimental arterial clamp 36 or to renal arterial stenosis. 30 The overdistension 3738 of these small arteries occurs in segmental fashion with vascular necrosis, [38][39][40] which allow red blood cells, plasma, and protein ultrafiltrates into the stretched segments of the wall.…”
Section: Arterial Pathology Of Lacunesmentioning
confidence: 99%
“…41 That other vessels are spared such injury is not easily explained. However, some findings 36,42 suggest that larger vessels are able to absorb enough in the subintima and in their thicker muscularis to resist such change, while the tiny cerebral cortical arteries of a size similar to the penetrators are protected by their more distal location. 37 Lipohyalinosis*"-" shares with fibrinoid necrosis some of the same histochemical, 43 electron-microscopic, 36, ** and immunofiuorescent 46 characteristics.…”
Section: Arterial Pathology Of Lacunesmentioning
confidence: 99%
“…Similar reactions have been described in rabbits (19 (20). The necessary combination of severe renal insufficiency and hypertension in the etiology of the malignant syndrome of renally ischemic animals (21,22), has been questioned as the result of experiments on rats, in which only one renal artery was constricted (23,24).. In the present study, there are definite indications that heterologous renin can precipitate cardiac and gastro-intestinal hemorrhages and necroses, in some dogs without severe hypertension or renal insufficiency.…”
Section: Discussionmentioning
confidence: 61%
“…13) and probably were responsible for the intestinal lesion. Goldblatt 9 has recently reported that intestinal bleeding is one 2 I12 EFFECT OF DIET ON RATS WITH NEPHITMS of the cardinal signs of the malignant phase of hypertension in dogs. While blood pressure readings were not made in the present experiment, hypertension was previously demonstrated in rats with chronic progressive nephritis of nephrotoxic origin.3…”
Section: Sadel and Farrmentioning
confidence: 99%